Environmentally friendly PUR hot melt adhesive and preparation method thereof
Through the reaction of scientifically proportioned polymers and composite materials, an environmentally friendly PUR hot melt adhesive with its own defoaming ability was developed, which solved the bubble generation, easy bulge, slow curing and unresisting of high temperatures in the existing PUR hot melt adhesive. The problem is that it achieves fast curing speed, strong adhesion and good aging resistance.
Patent Information
- Application Number
- CN202410881654.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-02
AI Technical Summary
The existing PUR hot melt adhesives have problems such as bubble generation, easy bulge, slow curing and unresisting of high temperatures, which limits their application.
Using scientifically proportioned polycarbonate diols, polyether polyols, terpene phenolic resins and modified isocyanates, montmorillonite/chitin-based porous materials/silica composites reacted under the action of a catalyst to obtain their own Environmentally friendly PUR hot melt adhesive with defoaming ability.
It achieves the effects of fast curing speed, strong adhesion and excellent aging resistance, avoiding bubble generation and bulging problems.
Smart Images

Figure BDA0004924723000000141 
Figure BDA0004924723000000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hot melt adhesives, and in particular to an environmentally friendly PUR hot melt adhesive and a preparation method thereof. Background Art
[0002] Hot melt adhesive is a thermoplastic polymer adhesive that changes its physical state with temperature within a certain temperature range. When heated, it becomes molten and fluid, and it is easy to infiltrate the surface of the substrate to achieve a good wetting state. After the temperature drops, it cools to a solid state. At this time, the adhesive film has strong tensile strength and elongation, forming a good adhesive joint, thereby providing good bonding strength. PUR hot melt adhesive has the advantages of excellent bonding performance, good weather resistance, green environmental protection, and suitability for mechanized and automated production. It is currently widely used in the automotive, home appliance, electronics and other industries.
[0003] However, PUR adhesives still have problems such as bubble generation, easy bulging, slow curing and high temperature resistance, which limit their application. It is necessary to improve these properties, break through the limitations, and develop PUR hot melt adhesive products with higher performance levels. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide an environmentally friendly PUR hot melt adhesive and a preparation method thereof, wherein the PUR hot melt adhesive will not produce bubbles during the curing process, and has a fast curing speed, good bonding strength, and excellent aging resistance.
[0005] To this end, the present invention adopts the following technical solutions:
[0006] The invention provides an environmentally friendly PUR hot melt adhesive, which comprises the following components in parts by weight: 20-50 parts of polycarbonate diol, 15-30 parts of polyether polyol, 15-30 parts of modified isocyanate, 2.5-15 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 0.5-5 parts of pentaerythritol diacrylate, 2-7 parts of terpene phenolic resin and 0.1-1.5 parts of catalyst.
[0007] Preferably, the modified isocyanate is aminosilane modified isocyanate, which is obtained by a mixed reaction of aminosilane and isocyanate, and the mass proportion of aminosilane in the modified isocyanate is 0.3-3%.
[0008] Preferably, the aminosilane is selected from at least one of γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and γ-aminopropylmethyldiethoxysilane.
[0009] Preferably, the method for preparing the montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps:
[0010] S1, preparing chitosan-based porous material: 1) dissolving chitosan powder with sodium hydroxide solution, stirring and reacting at 80-90° C. for 1-3 h, washing, filtering and drying to obtain positively charged chitosan; 2) placing the positively charged chitosan in a hydrothermal reactor, spraying 3 mol / L HCl solution, sealing, reacting at 70° C. for 3-5 h, washing with distilled water to neutrality after the reaction, freeze-drying, grinding, and passing through a 400-800 mesh sieve to obtain a chitosan-based porous material;
[0011] S2, preparing montmorillonite sheets: 1) placing the dried montmorillonite in a liquid nitrogen reaction bottle until the liquid nitrogen is completely vaporized, leaving it to stand, and taking it out after the temperature of the montmorillonite returns to room temperature, repeating the operation 3-10 times; 2) subjecting the montmorillonite in step (1) to ultrasonic vibration for 15-40 minutes to obtain montmorillonite nanosheets;
[0012] S3, dispersing the montmorillonite nanosheets in water, adding chitosan-based porous material and porous silica, stirring and reacting for 3-6 hours, filtering, and freeze-drying to obtain a montmorillonite / chitosan-based porous material / silicon dioxide composite material.
[0013] Preferably, in step S3, the mass ratio of the montmorillonite nanosheet, the chitosan-based porous material and the porous silica is (0.5-1):(1-10):(0.5-1).
[0014] Preferably, the particle size of the porous silica is 30-800 nm.
[0015] More preferably, the particle size of the porous silica is 50-300 nm.
[0016] Preferably, the number average molecular weight of the polycarbonate diol is 1000-3000.
[0017] Preferably, the polyether polyol is selected from at least one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol.
[0018] Preferably, the isocyanate is selected from one or more of 4,4'-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
[0019] Preferably, the catalyst includes one or more of dibutyltin dilaurate, tetrabutyl titanate, dimorpholinyl diethyl ether and N,N,N'-trimethyl-N'-hydroxyethyl-diaminoethyl ether.
[0020] The present invention also provides a method for preparing an environmentally friendly PUR hot melt adhesive, comprising the following steps:
[0021] (1) putting polycarbonate diol, polyether polyol and terpene phenolic resin into a reaction kettle, heating them to 110-120° C. to completely melt them, and vacuum dehydrating them under uniform stirring until the water content is less than 200 ppm;
[0022] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and the montmorillonite / chitin-based porous material / silicon dioxide composite material are placed in a reaction kettle, stirred and reacted for 1-2 hours under nitrogen protection, and then the catalyst is added and stirred and reacted for 20-60 minutes;
[0023] (3) Add pentaerythritol diacrylate, stir and react for 10-20 minutes, discharge the material, and seal and store in a moisture-proof manner.
[0024] In the above technical solution, as the content of pentaerythritol diacrylate increases, both the initial bonding strength and the final bonding strength of PUR show an increasing trend.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The invention adopts polycarbonate diol, polyether polyol, terpene phenolic resin and modified isocyanate, montmorillonite / chitin-based porous material / silicon dioxide composite material with scientific proportion to react under the action of catalyst to obtain polyurethane, and then modifies it with an appropriate amount of pentaerythritol diacrylate to obtain environmentally friendly PUR hot melt adhesive, which has self-defoaming ability, fast curing speed, strong adhesion and good aging resistance.
[0027] The present invention adopts aminosilane-modified isocyanate to improve water resistance and strength. The modified isocyanate reacts with polycarbonate diol and polyether polyol to obtain a polyurethane prepolymer with better flexibility.
[0028] The montmorillonite / chitosan-based porous material / silicon dioxide composite material provided by the present invention is prepared by reacting a delaminated montmorillonite nanosheet with a loose chitosan-based porous material and porous nano silicon dioxide. The composite material has a loose porous structure, which can rapidly burst bubbles generated during the curing process and play a defoaming role; the composite material has a large number of functional groups, which significantly improves the curing speed and bonding ability. The composite material has good compatibility with polyurethane materials and can be evenly distributed and bonded to the polyurethane molecular chain through chemical bonds, thereby improving the performance of the polyurethane and improving the aging resistance.
[0029] The present invention adopts pentaerythritol diacrylate to modify the polyurethane prepolymer, which can appropriately increase the crosslinking degree, obtain moderate viscosity, and further improve the bonding strength of the PUR hot melt adhesive.
[0030] In summary, the environmentally friendly PUR hot melt adhesive provided by the present invention has excellent comprehensive performance and has broad application prospects. DETAILED DESCRIPTION
[0031] Below by specific embodiment, the specific implementation mode of this explanation technical scheme is further described, these embodiments are for the detailed description of this technical scheme, rather than for limiting this technical scheme. Based on the embodiment in this description, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of this description. Unless otherwise specified, the reagent, method and equipment used in the present invention are conventional reagents, methods and equipment in the art, and the reagents and materials used in the following examples are all commercially available.
[0032] Polycarbonate diol CAS: 29862-10-0PCDL was purchased from Shandong Duolian Chemical Co., Ltd.
[0033] Polyether polyol PPG-3000 was purchased from Haian Petrochemical Plant, Jiangsu Province.
[0034] Terpene phenolic resin 803L was purchased from Shandong Senya New Materials Co., Ltd.
[0035] 4,4'-Dicyclohexylmethane diisocyanate was purchased from Hubei Watson Chemical Technology Co., Ltd.
[0036] 4,4'-Diphenylmethane diisocyanate was purchased from Shandong Xinwei Chemical Technology Co., Ltd.
[0037] Example 1
[0038] An environmentally friendly PUR hot melt adhesive comprises the following components in parts by weight: 40 parts of polycarbonate diol, 20 parts of polyether polyol PPG-3000, 15 parts of modified isocyanate, 10 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 3 parts of pentaerythritol diacrylate, 5 parts of terpene phenolic resin, and 0.8 parts of dibutyltin dilaurate.
[0039] The modified isocyanate is obtained by mixing γ-aminopropyltrimethoxysilane and 4,4'-dicyclohexylmethane diisocyanate, and the weight proportion of γ-aminopropyltrimethoxysilane in the modified isocyanate is 2%.
[0040] The preparation method of the above-mentioned montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps:
[0041] S1, preparation of chitosan-based porous material: 1) placing 20 g chitosan into 200 mL 40 wt% NaOH solution at 80° C. for reaction for 2 h, stirring at 800 rpm, washing with distilled water until neutral, filtering, and drying at 60° C. to obtain positively charged chitosan; 2) placing 2 g positively charged chitosan into 80 mL hydrothermal reactor, spraying 2 mL 3 mol / L HCl solution, sealing the hydrothermal reactor, placing it in an oven at 70° C. for reaction for 5 h, washing with distilled water until neutral, filtering with a 300 mesh sieve after the reaction, collecting the upper layer product and freeze-drying it with liquid nitrogen to obtain a chitosan-based porous material with a large specific surface area and a positive charge.
[0042] S2, preparation of montmorillonite sheet: 1) Weigh 5g of nano-montmorillonite, put it in a beaker, put it in a forced air drying oven, dry it at 60℃ for 8h, take out the montmorillonite, cool it to room temperature for use. Put the dried montmorillonite into a 1000mL conical flask, add 250mL of liquid nitrogen to the conical flask, let it stand after the liquid nitrogen is completely vaporized, and repeat the above vaporization-standing steps for a total of 10 times. 2) Put the obtained montmorillonite into a 180W ultrasonic cleaner for ultrasonic vibration for 15min to obtain montmorillonite nanosheets.
[0043] S3, by weight, disperse 1 part of montmorillonite nanosheets in water, add 10 parts of chitosan-based porous materials and 1 part of porous silica, stir and react for 3 hours, filter, and freeze-dry to obtain a montmorillonite / chitosan-based porous material / silica composite material.
[0044] The preparation method of the environmentally friendly PUR hot melt adhesive comprises the following steps:
[0045] (1) putting polycarbonate diol, polyether polyol PPG-3000, and terpene phenolic resin into a reaction kettle, heating to 118° C. to completely melt them, and vacuum dehydrating them under uniform stirring until the water content is less than 200 ppm;
[0046] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and the montmorillonite / chitin-based porous material / silicon dioxide composite material were placed in a reaction kettle, stirred and reacted for 1.5 hours under nitrogen protection, and then dibutyltin dilaurate was added and stirred and reacted for 30 minutes;
[0047] (3) Add pentaerythritol diacrylate, stir for 20 minutes, discharge the material, and seal it to prevent moisture.
[0048] Example 2
[0049] An environmentally friendly PUR hot melt adhesive comprises the following components in parts by weight: 50 parts of polycarbonate diol, 30 parts of polyether polyol PPG-3000, 20 parts of modified isocyanate, 8 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 3 parts of pentaerythritol diacrylate, 5 parts of terpene phenolic resin, and 0.8 parts of dibutyltin dilaurate.
[0050] The modified isocyanate is obtained by mixing γ-aminopropyltrimethoxysilane and 4,4'-dicyclohexylmethane diisocyanate, and the weight proportion of γ-aminopropyltrimethoxysilane in the modified isocyanate is 2%.
[0051] The preparation method of the above-mentioned montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps:
[0052] S1, preparation of chitosan-based porous material: 1) placing 20 g chitosan into 200 mL 40 wt% NaOH solution at 80° C. for reaction for 2 h, stirring at 800 rpm, washing with distilled water until neutral, filtering, and drying at 60° C. to obtain positively charged chitosan; 2) placing 2 g positively charged chitosan into 80 mL hydrothermal reactor, spraying 2 mL 3 mol / L HCl solution, sealing the hydrothermal reactor, placing it in an oven at 70° C. for reaction for 5 h, washing with distilled water until neutral, filtering with a 300 mesh sieve after the reaction, collecting the upper layer product and freeze-drying it with liquid nitrogen to obtain a chitosan-based porous material with a large specific surface area and a positive charge.
[0053] S2, preparation of montmorillonite sheet: 1) Weigh 5g of nano-montmorillonite, put it in a beaker, put it in a forced air drying oven, dry it at 60℃ for 8h, take out the montmorillonite, cool it to room temperature for use. Put the dried montmorillonite into a 1000mL conical flask, add 250mL of liquid nitrogen to the conical flask, let it stand after the liquid nitrogen is completely vaporized, and repeat the above vaporization-standing steps for a total of 10 times. 2) Put the obtained montmorillonite into a 180W ultrasonic cleaner for ultrasonic vibration for 15min to obtain montmorillonite nanosheets.
[0054] S3, by weight, disperse 1 part of montmorillonite nanosheets in water, add 10 parts of chitosan-based porous material and 0.5 parts of porous silica, stir and react for 3 hours, filter, and freeze-dry to obtain a montmorillonite / chitosan-based porous material / silica composite material.
[0055] The preparation method of the environmentally friendly PUR hot melt adhesive comprises the following steps:
[0056] (1) putting polycarbonate diol, polyether polyol PPG-3000, and terpene phenolic resin into a reaction kettle, heating to 118° C. to completely melt them, and vacuum dehydrating them under uniform stirring until the water content is less than 200 ppm;
[0057] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and the montmorillonite / chitin-based porous material / silicon dioxide composite material were placed in a reaction kettle, stirred and reacted for 1.5 hours under nitrogen protection, and then dibutyltin dilaurate was added and stirred and reacted for 30 minutes;
[0058] (3) Add pentaerythritol diacrylate, stir for 20 minutes, discharge the material, and seal it to prevent moisture.
[0059] Example 3
[0060] An environmentally friendly PUR hot melt adhesive comprises the following components in parts by weight: 30 parts of polycarbonate diol, 30 parts of polyether polyol, 15 parts of aminosilane modified isocyanate, 5 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 2 parts of pentaerythritol diacrylate, 3 parts of terpene phenolic resin, and 0.5 parts of a catalyst.
[0061] The modified isocyanate is obtained by mixing γ-aminopropyltrimethoxysilane and 4,4'-dicyclohexylmethane diisocyanate, and the weight proportion of γ-aminopropyltrimethoxysilane in the modified isocyanate is 2%.
[0062] The preparation method of the above-mentioned montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps:
[0063] S1, preparation of chitosan-based porous material: 1) placing 20 g chitosan into 200 mL 40 wt% NaOH solution at 80° C. for reaction for 2 h, stirring at 800 rpm, washing with distilled water until neutral, filtering, and drying at 60° C. to obtain positively charged chitosan; 2) placing 2 g positively charged chitosan into 80 mL hydrothermal reactor, spraying 2 mL 3 mol / L HCl solution, sealing the hydrothermal reactor, placing it in an oven at 70° C. for reaction for 5 h, washing with distilled water until neutral, filtering with a 300 mesh sieve after the reaction, collecting the upper layer product and freeze-drying it with liquid nitrogen to obtain a chitosan-based porous material with a large specific surface area and a positive charge.
[0064] S2, preparation of montmorillonite sheet: 1) Weigh 5g of nano-montmorillonite, put it in a beaker, put it in a forced air drying oven, dry it at 60℃ for 8h, take out the montmorillonite, cool it to room temperature for use. Put the dried montmorillonite into a 1000mL conical flask, add 250mL of liquid nitrogen to the conical flask, let it stand after the liquid nitrogen is completely vaporized, and repeat the above vaporization-standing steps for a total of 10 times. 2) Put the obtained montmorillonite into a 180W ultrasonic cleaner for ultrasonic vibration for 15min to obtain montmorillonite nanosheets.
[0065] S3, by weight, disperse 1 part of montmorillonite nanosheets in water, add 10 parts of chitosan-based porous materials and 1 part of porous silica, stir and react for 3 hours, filter, and freeze-dry to obtain a montmorillonite / chitosan-based porous material / silica composite material.
[0066] The preparation method of the environmentally friendly PUR hot melt adhesive comprises the following steps:
[0067] (1) putting polycarbonate diol, polyether polyol PPG-3000, and terpene phenolic resin into a reaction kettle, heating to 118° C. to completely melt them, and vacuum dehydrating them under uniform stirring until the water content is less than 200 ppm;
[0068] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and the montmorillonite / chitin-based porous material / silicon dioxide composite material were placed in a reaction kettle, stirred and reacted for 1.5 hours under nitrogen protection, and then dibutyltin dilaurate was added and stirred and reacted for 30 minutes;
[0069] (3) Add pentaerythritol diacrylate, stir for 20 minutes, discharge the material, and seal it to prevent moisture.
[0070] Example 4
[0071] An environmentally friendly PUR hot melt adhesive comprises the following components in parts by weight: 50 parts of polycarbonate diol, 15 parts of polyether polyol, 16 parts of aminosilane modified isocyanate, 5 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 4 parts of pentaerythritol diacrylate, 5 parts of terpene phenolic resin, and 0.7 parts of a catalyst.
[0072] The modified isocyanate is obtained by a mixed reaction of γ-aminopropyltrimethoxysilane and 4,4'-diphenylmethane diisocyanate, and the weight proportion of γ-aminopropyltrimethoxysilane in the modified isocyanate is 2.5%.
[0073] The preparation method of the above-mentioned montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps:
[0074] S1, preparation of chitosan-based porous material: 1) placing 20 g chitosan into 200 mL 40 wt% NaOH solution at 80° C. for reaction for 2 h, stirring at 800 rpm, washing with distilled water until neutral, filtering, and drying at 60° C. to obtain positively charged chitosan; 2) placing 2 g positively charged chitosan into 80 mL hydrothermal reactor, spraying 2 mL 3 mol / L HCl solution, sealing the hydrothermal reactor, placing it in an oven at 70° C. for reaction for 5 h, washing with distilled water until neutral, filtering with a 300 mesh sieve after the reaction, collecting the upper layer product and freeze-drying it with liquid nitrogen to obtain a chitosan-based porous material with a large specific surface area and a positive charge.
[0075] S2, preparation of montmorillonite sheet: 1) Weigh 5g of nano-montmorillonite, put it in a beaker, put it in a forced air drying oven, dry it at 60℃ for 8h, take out the montmorillonite, cool it to room temperature for use. Put the dried montmorillonite into a 1000mL conical flask, add 250mL of liquid nitrogen to the conical flask, let it stand after the liquid nitrogen is completely vaporized, and repeat the above vaporization-standing steps for a total of 10 times. 2) Put the obtained montmorillonite into a 180W ultrasonic cleaner for ultrasonic vibration for 15min to obtain montmorillonite nanosheets.
[0076] S3, by weight, disperse 1 part of montmorillonite nanosheets in water, add 5 parts of chitosan-based porous material and 1 part of porous silica, stir and react for 3 hours, filter, and freeze-dry to obtain a montmorillonite / chitosan-based porous material / silica composite material.
[0077] The preparation method of the environmentally friendly PUR hot melt adhesive comprises the following steps:
[0078] (1) putting polycarbonate diol, polyether polyol PPG-3000, and terpene phenolic resin into a reaction kettle, heating to 118° C. to completely melt them, and vacuum dehydrating them under uniform stirring until the water content is less than 200 ppm;
[0079] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and the montmorillonite / chitin-based porous material / silicon dioxide composite material were placed in a reaction kettle, stirred and reacted for 1.5 hours under nitrogen protection, and then dibutyltin dilaurate was added and stirred and reacted for 30 minutes;
[0080] (3) Add pentaerythritol diacrylate, stir for 20 minutes, discharge the material, and seal it to prevent moisture.
[0081] Example 5
[0082] An environmentally friendly PUR hot melt adhesive comprises the following components in parts by weight: 40 parts of polycarbonate diol, 30 parts of polyether polyol, 20 parts of aminosilane modified isocyanate, 10 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 5 parts of pentaerythritol diacrylate, 5 parts of terpene phenolic resin and 1 part of catalyst.
[0083] The modified isocyanate is obtained by mixing γ-aminopropyltrimethoxysilane and 4,4'-dicyclohexylmethane diisocyanate, and the weight proportion of γ-aminopropyltrimethoxysilane in the modified isocyanate is 2%.
[0084] The preparation method of the above-mentioned montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps:
[0085] S1, preparation of chitosan-based porous material: 1) placing 20 g chitosan into 200 mL 40 wt% NaOH solution at 80° C. for reaction for 2 h, stirring at 800 rpm, washing with distilled water until neutral, filtering, and drying at 60° C. to obtain positively charged chitosan; 2) placing 2 g positively charged chitosan into 80 mL hydrothermal reactor, spraying 2 mL 3 mol / L HCl solution, sealing the hydrothermal reactor, placing it in an oven at 70° C. for reaction for 5 h, washing with distilled water until neutral, filtering with a 300 mesh sieve after the reaction, collecting the upper layer product and freeze-drying it with liquid nitrogen to obtain a chitosan-based porous material with a large specific surface area and a positive charge.
[0086] S2, preparation of montmorillonite sheet: 1) Weigh 5g of nano-montmorillonite, put it in a beaker, put it in a forced air drying oven, dry it at 60℃ for 8h, take out the montmorillonite, cool it to room temperature for use. Put the dried montmorillonite into a 1000mL conical flask, add 250mL of liquid nitrogen to the conical flask, let it stand after the liquid nitrogen is completely vaporized, and repeat the above vaporization-standing steps for a total of 10 times. 2) Put the obtained montmorillonite into a 180W ultrasonic cleaner for ultrasonic vibration for 15min to obtain montmorillonite nanosheets.
[0087] S3, by weight, disperse 1.5 parts of montmorillonite nanosheets in water, add 7 parts of chitosan-based porous material and 1 part of porous silica, stir and react for 3 hours, filter, and freeze-dry to obtain a montmorillonite / chitosan-based porous material / silica composite material.
[0088] The preparation method of the environmentally friendly PUR hot melt adhesive comprises the following steps:
[0089] (1) putting polycarbonate diol, polyether polyol PPG-3000, and terpene phenolic resin into a reaction kettle, heating to 118° C. to completely melt them, and vacuum dehydrating them under uniform stirring until the water content is less than 200 ppm;
[0090] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and the montmorillonite / chitin-based porous material / silicon dioxide composite material were placed in a reaction kettle, stirred and reacted for 1.5 hours under nitrogen protection, and then dibutyltin dilaurate was added and stirred and reacted for 30 minutes;
[0091] (3) Add pentaerythritol diacrylate, stir for 20 minutes, discharge the material, and seal it to prevent moisture.
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 1 is that no montmorillonite / chitosan-based porous material / silicon dioxide composite material is added, and the other aspects are the same.
[0094] The preparation method is the same as Example 1.
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that the montmorillonite / chitosan-based porous material / silicon dioxide composite material is replaced by an equal weight portion of montmorillonite, and the montmorillonite is not subjected to delamination treatment, and the other aspects are the same.
[0097] The preparation method is the same as Example 1.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that the montmorillonite / chitosan-based porous material / silicon dioxide composite material is replaced with silicon dioxide in equal parts by weight, and the other parts are the same.
[0100] The preparation method is the same as Example 1.
[0101] Comparative Example 4
[0102] The difference between this comparative example and Example 1 is that the montmorillonite / chitosan-based porous material / silicon dioxide composite material is replaced by equal parts by weight of montmorillonite and silicon dioxide, the weight ratio of montmorillonite to silicon dioxide is 1:1, and the other parts are the same.
[0103] The preparation method is the same as Example 1.
[0104] Comparative Example 5
[0105] The difference between this comparative example and Example 1 is that unmodified isocyanate is used, and the other aspects are the same.
[0106] The preparation method is the same as Example 1.
[0107] Comparative Example 6
[0108] This comparative example is different from Example 1 in that pentaerythritol diacrylate is not added, and the other aspects are the same.
[0109] The preparation method is the same as Example 1.
[0110] Comparative Example 7
[0111] The difference between this comparative example and Example 1 is that the preparation method of the environmentally friendly PUR hot melt adhesive is different.
[0112] The preparation method of the environmentally friendly PUR hot melt adhesive comprises the following steps:
[0113] (1) polycarbonate diol, polyether polyol PPG-3000, terpene phenolic resin, and pentaerythritol diacrylate are placed in a reaction kettle, heated to 118° C. to completely melt, and vacuum-dehydrated under uniform stirring until the water content is less than 200 ppm;
[0114] (2) After de-vacuuming with dry nitrogen, the modified isocyanate and montmorillonite / chitin-based porous material / silicon dioxide composite material were placed in a reactor, stirred and reacted for 1.5 hours under nitrogen protection, and then dibutyltin dilaurate was added and stirred and reacted for 30 minutes. The material was discharged and sealed for moisture-proof storage.
[0115] The environmentally friendly PUR hot melt adhesives obtained in Examples 1-5 and Comparative Examples 1-7 were made into corresponding shapes according to different standards and subjected to the following performance tests:
[0116] (1) Bubble size: Heat the hot melt adhesive at 130°C and evenly coat it on an aluminum sheet that has been pretreated with 99% alcohol. The film thickness is controlled to be 2 mm. After the film is completely cured, count the number of bubbles per unit area. The aluminum sheet is 25 mm wide and 200 mm long. Cut off a 10 mm*10 mm film in the middle and count the number of bubbles. The bubbles are small and dense, and can be counted with a magnifying glass and a counter.
[0117] (2) Initial bond strength: After the shear specimens were cured at 25°C @ 50% RH for 1 min, they were tested in accordance with standard GB / T7124-2008 “Test method for tensile shear strength of adhesives”.
[0118] (3) 1h bonding strength: After the shear specimens were cured at 25°C @ 50% RH for 1h, they were tested in accordance with standard GB / T7124-2008 “Test method for tensile shear strength of adhesives”.
[0119] (4) Final adhesion strength: After the shear specimens were cured at 25°C @ 50% RH for 7 days, they were tested in accordance with standard GB / T7124-2008 “Test method for tensile shear strength of adhesives”.
[0120] (5) Adhesive strength after aging for 7 days: After the fully cured shear specimens were placed in an oven at 85°C / 85RH% for 7 days, the shear specimens were taken out and placed at room temperature for 2 hours and tested in accordance with standard GB / T 7124-2008 “Determination of tensile shear strength of adhesives”.
[0121] The test results are shown in Table 1.
[0122] Table 1 Performance test results
[0123]
[0124]
[0125] It can be seen from Table 1 that the PUR hot melt adhesive provided by Examples 1-5 of the present invention has no residual bubbles and no bulging during the curing process; the initial bonding strength can reach 1.84-2.42 MPa, the 1h bonding strength can reach 6.83-8.41 MPa, the final bonding strength can reach 8.51-9.62 MPa, the curing speed is fast, and the bonding strength after curing is high; after aging at 85°C / 85RH% for 7d, the bonding strength can reach 8.48-9.58 MPa, and the aging resistance is good.
[0126] Comparative Example 1 Compared with Example 1, no montmorillonite / chitosan-based porous material / silicon dioxide composite material was added. After curing, there were 14 bubbles, the initial adhesive strength was 1.93 MPa, the 1h bonding strength was 1.93 MPa, and the final bonding strength was 7.12 MPa. The curing speed was obviously slower and the bonding strength was lower. After aging for 7 days at 85°C / 85RH%, the bonding strength was 6.96 MPa, and the anti-aging ability became worse. It shows that adding montmorillonite / chitosan-based porous material / silicon dioxide composite material can quickly break the bubbles in the curing process without bulging, has a significant defoaming effect, and can significantly improve the bonding strength and aging resistance.
[0127] Comparative Example 2 Compared with Example 1, the montmorillonite / chitosan-based porous material / silicon dioxide composite material was replaced with montmorillonite of equal weight. After curing, there were 8 bubbles, the initial bonding strength was 0.05 MPa, the 1h bonding strength was 1.06 MPa, and the final bonding strength was 7.54 MPa, which was obviously slower in curing speed and lower in bonding strength. It is shown that the montmorillonite / chitosan-based porous material / silicon dioxide composite material of the present invention has a better defoaming effect than the inorganic filler montmorillonite, and can better improve the bonding strength.
[0128] Comparative Example 3 Compared with Example 1, the montmorillonite / chitosan-based porous material / silicon dioxide composite material was replaced with an equal weight portion of silicon dioxide. After curing, there were 3 bubbles, the initial bonding strength was 0.36 MPa, the 1h bonding strength was 2.87 MPa, and the final bonding strength was 7.96 MPa. The curing speed was slower and the bonding strength was lower. This shows that although silicon dioxide has a good defoaming effect, it is still not as good as the montmorillonite / chitosan-based porous material / silicon dioxide composite material; silicon dioxide can improve the bonding ability, but it is still not as good as the montmorillonite / chitosan-based porous material / silicon dioxide composite material.
[0129] Comparative Example 4 Compared with Example 1, the montmorillonite / chitosan-based porous material / silicon dioxide composite material was replaced with equal weight parts of montmorillonite and silicon dioxide in a weight ratio of 1:1. After curing, there was 1 blister, the initial adhesive strength was 0.19 MPa, the 1h adhesive strength was 1.76 MPa, and the final adhesive strength was 7.63 MPa. The defoaming effect was better, but the curing speed was slower and the adhesive strength was lower. It shows that the montmorillonite / chitosan-based porous material / silicon dioxide composite material has a better defoaming effect and can more significantly improve the bonding performance than the combination of montmorillonite and silicon dioxide.
[0130] Compared with Example 1, Comparative Example 5 uses unmodified isocyanate, with an initial bonding strength of 1.12 MPa, a 1h bonding strength of 5.67 MPa, and a final bonding strength of 8.86 MPa, and a slower curing speed and lower bonding strength, indicating that the use of modified isocyanate can improve bonding performance.
[0131] Compared with Example 1, in Comparative Example 6, no pentaerythritol diacrylate was added, and the initial bonding strength was 1.45 MPa, the 1h bonding strength was 6.49 MPa, and the final bonding strength was 9.05 MPa, which was lower. This indicates that the use of pentaerythritol diacrylate to modify the polyurethane obtained in step (2) can further improve the bonding performance.
[0132] Comparative Example 7 Compared with Example 1, the preparation method of environmentally friendly PUR hot melt adhesive is different. Pentaerythritol diacrylate is added to the reaction in step (1). The initial adhesive strength is 0.67 MPa, the 1h adhesive strength is 3.28 MPa, and the final adhesive strength is 9.38 MPa, which is lower. This shows that the adhesive performance of the polyurethane obtained by adding pentaerythritol diacrylate to the reaction in step (1) is not as good as the hot melt adhesive obtained by modifying the polyurethane obtained in step (2) with pentaerythritol diacrylate.
[0133] In summary, the PUR hot melt adhesive provided by the present invention has a fast curing speed, a smooth surface after curing without bulging, strong bonding performance, good aging resistance, and has good application prospects.
[0134] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A PUR hot melt adhesive, characterized in that: The invention comprises the following components in parts by weight: 20-50 parts of polycarbonate diol, 15-30 parts of polyether polyol, 15-30 parts of modified isocyanate, 2.5-15 parts of montmorillonite / chitin-based porous material / silicon dioxide composite material, 0.5-5 parts of pentaerythritol diacrylate, 2-7 parts of terpene phenolic resin and 0.1-1.5 parts of catalyst; the modified isocyanate is aminosilane modified isocyanate, which is obtained by mixed reaction of aminosilane and isocyanate, and the mass proportion of aminosilane in the modified isocyanate is 0.3-3%; The aminosilane is selected from at least one of γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and γ-aminopropylmethyldiethoxysilane; the preparation method of the montmorillonite / chitosan-based porous material / silicon dioxide composite material comprises the following steps: S1, preparing the chitosan-based porous material: 1) dissolving chitosan powder in sodium hydroxide solution, stirring and reacting at 80-90° C. for 1-3 hours, washing, filtering, and drying to obtain positively charged chitosan; 2) placing the positively charged chitosan in a hydrothermal reactor and spraying 3 mol / L HCl solution, sealed, reacted at 70°C for 3-5h, washed with distilled water until neutral after the reaction, freeze-dried, ground, and passed through a 400-800 mesh sieve to obtain a chitosan-based porous material; S2, preparing montmorillonite sheets: 1) placing the dried montmorillonite in a liquid nitrogen reaction bottle until the liquid nitrogen is completely vaporized, standing, and taking out after the montmorillonite temperature returns to room temperature, and repeating the operation 3-10 times; 2) subjecting the montmorillonite in step (1) to ultrasonic vibration for 15-40min to obtain a montmorillonite nanosheet; S3, dispersing the montmorillonite nanosheet in water, adding the chitosan-based porous material and porous silica, stirring for 3-6h, filtering, freeze-drying, and obtaining a montmorillonite / chitosan-based porous material / silicon dioxide composite material; the montmorillonite nanosheet and chitosan-based porous material in step S3 are prepared. The mass ratio of the material and the porous silica is (0.5-1):(1-10):(0.5-1); the preparation method of the PUR hot melt adhesive is characterized in that it includes the following steps: (1) putting polycarbonate diol, polyether polyol, and terpene phenolic resin into a reactor, heating them to 110-120°C to completely melt them, and vacuum dehydrating them under uniform stirring conditions until the moisture content is less than 200ppm; (2) after de-vacuuming with dry nitrogen, the modified isocyanate and montmorillonite / chitin-based porous material / silica composite material are put into the reactor, stirring and reacting for 1-2 hours under nitrogen protection, and then adding a catalyst and stirring and reacting for 20-60 minutes; (3) adding pentaerythritol diacrylate, stirring and reacting for 10-20 minutes, discharging the material, and sealing and moisture-proofing for storage.
2. The PUR hot melt adhesive according to claim 1, characterized in that: The number average molecular weight of the polycarbonate diol is 1000-3000.
3. The PUR hot melt adhesive according to claim 1, characterized in that: The polyether polyol is selected from at least one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol.
4. The PUR hot melt adhesive according to claim 1, characterized in that: The isocyanate is selected from one or more of 4,4'-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
5. The PUR hot melt adhesive according to claim 1, characterized in that: The catalyst includes one or more of dibutyltin dilaurate, tetrabutyl titanate, dimorpholinyl diethyl ether and N,N,N'-trimethyl-N'-hydroxyethyl-diaminoethyl ether.
Citation Information
Patent Citations
Carbon dioxide-based reactive polyurethane hot melt adhesive and preparation method thereof
CN116333663A
Clay-polyurethane nano composite and method forpreparing the same
KR1020050088042A